PENGARUH APLIKASI H2O2 35 % PADA GINGIVA TIKUS PUTIH JANTAN (Rattus norvegicus) - A A Kompiang Martini (Interdental: Jurnal Kedokteran Gigi, 2017)
Teeth whitening technique has been known since 1989. The in-officebleaching techniques using hydrogen peroxide (H2O2), H2O2 useful as tooth whitening experience discoloration or stainning on the teeth. However, if the use of hydrogen peroxide (H2O2) is not done carefully it can lead to irritation of the soft tissues of the oral cavity. Hydrogen peroxide (H2O2) is toxic and side effects are irritation of the gingiva to cause inflammation of gingiva.Gingivitis caused by various factors both exogenous and endogenous factors. Endogenous factors such as tartar, tooth crowding, hormonal, stress and microorganisms, exogenous factors caused by mechanical trauma, thermal, chemical, infection and malnutrition. Gingivitis is a complex response of tissue to injury that involves changes in the cells, humoral, and which is an inflammatory vascular. Neutrophils are the most prominent cells in acute inflammation. Neutrophil granules derived from neutral in sitoplasma. Based these problems, preliminary research proved that induction of H2O2 can cause inflammation of the gingiva. This is evidenced by the preliminary study using 6 male rats (Rattusnorvegicus) Wistar strain, divided into two groups: a control group (normal mice without induction H2O235%) and treatment groups (rats with induced H2O2 35%). The researchwas carried out as randomized Post test only control group design. The results showed the average number of neutrophils in the control group (11 cells per five field of view), while the treatment group (119 cells per five field of view). This shows that the treatment group contained significantly increase neutrophil cells.